Hard core logo - MacDonald, Bruce 1959-; Rennie, Callum Keith; Dillon, Hugh R. 1963-; Pyper-Ferguson, John (SPVision, 2005)
Specials: Musikvideos, audio commentary, cast & crew biographies, teaser
Komödie, Drama, Musik
Keywords: Reunions -- Drama.; Punk rock musicians -- Drama.; Documentary-style films.; Feature films.; Rockgruppe; Punk Rock; Dokumentarischer Spielfilm; Wiederbegegnung; Kanada; Film; DVD-Video